Stock price volatility following dividend announcements: A systematic literature review - Yunarni, Baiq Reinelda Tri; Fadah, Isti; Utami, Elok Sri; Puspitasari, Novi (Edelweiss Applied Science and Technology, 2025)
This study explores the impact of dividend announcements on stock price volatility at the Indonesia Stock Exchange, focusing on the critical period around the cum date and ex-date. Utilizing a systematic literature review method, this study integrates findings from various prior research efforts to deepen the understanding of how dividend announcements influence stock prices, especially for stocks with high dividend yields and large Dividends Per Share (DPS). The analysis was conducted by comparing stock price data before and after announcements to assess volatility and market reactions. The findings reveal that dividend announcements often act as catalysts that enhance stock prices. However, there is a significant increase in volatility approaching the cum date and ex-date, with a tendency for stock prices to decline. This suggests that investors might opt for exit strategies to leverage these volatile conditions. These findings imply the importance of timing in making investment decisions related to dividend announcements. The study is limited to the analysis of stocks on the Indonesia Stock Exchange and does not explore the influence of external factors that might impact stock price volatility. Therefore, the results may not be fully generalizable to other markets. This research offers valuable insights for investors and regulators in understanding the influence of dividend policies on stock market dynamics.